2021
DOI: 10.3390/polym14010097
|View full text |Cite
|
Sign up to set email alerts
|

Toward Polymeric and Polymer Composites Impeller Fabrication

Abstract: Impellers are referred to as a core component of turbomachinery. The use of impellers in various applications is considered an integral part of the industry. So, increased performance and the optimization of impellers have been the center of attention of a lot of studies. In this regard, studies have been focused on the improvement of the efficiency of rotary machines through aerodynamic optimization, using high-performance materials and suitable manufacturing processes. As such, the use of polymers and polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 126 publications
0
10
0
Order By: Relevance
“…Generally, in this method, fabrication of the part completed by placing one layer of material on top of the other. 1,2 Among the various methods in 3D printing, stereolithography (SLA) due to the high accuracy, smooth surface finishing, the ability to produce transparent objects, and the incorporation of fine details, for example, compared to the fused deposition modeling has been the center of attention of studies. [3][4][5] In this method scanning the resin surface by a laser, which is programmed before, can cause polymerization or cross-linking and leads to the fabrication of the parts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, in this method, fabrication of the part completed by placing one layer of material on top of the other. 1,2 Among the various methods in 3D printing, stereolithography (SLA) due to the high accuracy, smooth surface finishing, the ability to produce transparent objects, and the incorporation of fine details, for example, compared to the fused deposition modeling has been the center of attention of studies. [3][4][5] In this method scanning the resin surface by a laser, which is programmed before, can cause polymerization or cross-linking and leads to the fabrication of the parts.…”
Section: Introductionmentioning
confidence: 99%
“…Three‐dimensional (3D)‐printing technology has been one of the most important processes that have undergone changes and have attracted a lot of attention. Generally, in this method, fabrication of the part completed by placing one layer of material on top of the other 1,2 . Among the various methods in 3D printing, stereolithography (SLA) due to the high accuracy, smooth surface finishing, the ability to produce transparent objects, and the incorporation of fine details, for example, compared to the fused deposition modeling has been the center of attention of studies 3–5 .…”
Section: Introductionmentioning
confidence: 99%
“…After completion, the structure can be manually or chemically removed from the print platform by destroying the support structure [25,[55][56][57]. Fused deposition modeling (FDM) or material extrusion additive manufacturing are other names for this process that are permissible in Each tensile sample of PETG carbon fiber takes a minimum of 9 minutes and a maximum of 10 min for printing the ASTM D638.…”
Section: Fabrication and Testingmentioning
confidence: 99%
“…Each polymer raw material has its unique properties, for example, PLA is a biodegradable material [44], and ABS is a toxic material [45]. So, it is used in many applications like medical [46], pipe making [47], and impeller making [48] based on the raw material properties. A previous literature review revealed that the FDM-fabricated impeller of the rotodynamic hydraulic pump performed similarly to the original impeller.…”
Section: Materials Extrusion Process (Polymer Technology)mentioning
confidence: 99%